Theory of literature and other critical writings - Natsume, Sōseki 1867-1916 (Weatherhead books on Asia, 2009)
Natsume Soseki (1867-1916) was the foremost Japanese novelist of the twentieth century, known for such highly acclaimed works as Kokoro, Sanshiro, and I Am a Cat. Yet he began his career as a literary theorist and scholar of English literature. In 1907, he published Theory of Literature, a remarkably forward-thinking attempt to understand how and why we read. The text anticipates by decades the ideas and concepts of formalism, structuralism, reader-response theory, and postcolonialism, as well as cognitive approaches to literature that are only now gaini.